Microbiological quality and physicochemical characterization of Brazilian bee pollen - Arruda, Vanilda Aparecida Soares de (2018)
Bee Research Association. Sixty-two commercial samples of dehydrated bee pollen (Apis mellifera bees) collected in Brazil (eight states and the Federal District) were analyzed for commercial quality (moisture, ash, lipids, proteins, and carbohydrates), and hygiene (aerobic mesophiles, yeasts and molds, coliforms, Escherichia coli, Staphylococcus aureus and sulfite-reducing Clostridium). The analyzed samples were within the regulatory limits established by the legislation for ash, lipid and protein, except for moisture content. The analyzed hygiene parameters evaluated for bee pollen are not regulated by the Brazilian legislation, and the data discussed can contribute to regulatory agencies. Only moderate and weak correlations were observed between dehydrated pollen samples and the parameters evaluated.